Ni-Catalyzed Reductive Difunctionalization of Alkenes - Ping, Yuanyuan; Kong, Wangqing (Synthesis, 2020)
Alkene difunctionalization represents one of the most efficient methods to synthesize highly functionalized molecules from simple and readily available starting materials. In contrast to the well-established redox-neutral alkene difunctionalization reactions, reductive alkene difunctionalization, which simultaneously introduces two electrophiles on both sides of the double bond, has been much less developed, especially in enantioselective manner. This review summarizes recent advances in the nickel-catalyzed reductive difunctionalization of alkenes and highlights the enantioselective transformations.1 Introduction2 Nickel-Catalyzed Racemic Reductive Difunctionalization of Alkenes3 Nickel-Catalyzed Enantioselective Reductive Difunctionalization of Alkenes3.1 Diarylation of Alkenes3.2 Aryl-alkenylation of Alkenes3.3 Aryl-monofluoroalkenylation of Alkenes3.4 Reductive Cyclization/Coupling with Alkynyl Bromides or Asymmetric Internal Alkynes3.5 Aryl-alkylation of Alkenes3.6 Aryl-amination of Alkenes4 Summary and Outlook
Keywords: nickel catalysis; alkene difunctionalization; reductive cross-coupling; enantioselectivity; Heck cyclization